Evaluation of Corneal Epithelial Thickness and Dry Eye Disease Tests in Thalassemic Adolescents - Ebeid WM (Dove Medical Press, 2021)
Weam Mohamed Ebeid,1 Mahmoud Adel Kenny,2 Tamer AbdelFattah Badran1 1Department of Ophthalmology, Faculty of Medicine, Ain Shams University, Cairo, Egypt; 2Department of Pediatrics, Faculty of Medicine, Ain Shams University, Cairo, EgyptCorrespondence: Weam Mohamed EbeidFaculty of Medicine, Ain Shams University, 78 First District, Fifth Settlement, Cairo, 11861, EgyptTel +20 1003785838Email weam.ebeid@med.asu.edu.egPurpose: To assess dry eye disease (DED) in thalassemic adolescents by evaluating corneal epithelial thickness (CET) and various dry eye clinical tests and correlate them to tissue iron overload.Methods: The study included 120 Beta-thalassemia patients (11 to 18 years) and 120 matched controls. CET maps were captured using anterior segment optical coherence tomography. OSDI questionnaire was completed. Dry eye tests included Schirmer test, tear film breakup time ‎‎ (TBUT), and ocular surface staining (OSS) with fluorescein and lissamine green. We recorded serum ferritin ‎level, and liver iron concentration (LIC) measured by magnetic resonance imaging.Results: Superior and inferior CET was thinner, while map standard deviation (MSD) was higher in thalassemics compared to controls (all P‎< 0.001‎). Thalassemic group also showed higher OSDI scores‎ (P‎< 0.001), shorter TBUT ‎‎(P‎< 0.001‎), and higher OSS grades (P‎< 0.001‎). Both superior and inferior CET was correlated positively with TBUT, and negatively with OSS (all P < 0.001). Serum ferritin and LIC showed negative correlations with CET (superior and inferior, both P< 0.001), positive correlations with MSD, P< 0.001, as well as with TBUT (P< 0.001), OSS ‎(P< 0.001), and OSDI scores (P< 0.001).Conclusion: Thalassemic adolescents had thinner CET with higher thickness’ variability, shorter TBUT and more marked OSS‎ than controls. Correlation of higher serum ferritin and hepatic iron overload with irregular epithelial thinning and more affected dry eye tests results supports our hypothesis that high tissue iron levels could play a pivotal role in DED pathogenesis in thalassemic patients.Keywords: dry eye, thalassemia major, corneal epithelial map, OSDI questionnaire, anterior segment optic coherence tomography